Voices in the purple haze underground radio and the sixties - Keith, Michael C. 1945- (Praeger, 1997)
During the fateful summer of 1966, a handful of restless and frustrated deejays in New York and San Francisco began to conceive of a whole new brand of radio, one which would lead to the reinvention of contemporary music programming. Gone were the screaming deejays, the two minute doowop hits, and the goofy jingles. In were the counterculture sounds and sentiments that had seldom, if ever, made it to commercial radio. This new and unorthodox form of radio - this radical departure from the Top 40 establishment - reflected the social and cultural unrest of the period. Underground radio had been born of a desire to restore substance and meaning to a medium that had fallen victim to the bottom-line dictates of an industry devoted to profit. In this compelling and intriguing account of the counter-culture radio movement, over 30 pioneers of the underground airwaves share insights and observations, and tell it like it was.
Keywords: Geschichte 1900-2000; Geschichte 1960-1970; Piratenzenders; Radio; Geschichte; Alternative radio broadcasting -- United States -- History -- 20th century; Subculture -- United States -- History -- 20th century; Hörfunk; Alternativbewegung; USA; United States -- Social conditions -- 1960-1980